Modelling of dragline boom structure - Shukla A.; Rai P. (My University, 2025)
Draglines are the one of the most significant and biggest equipment used in the opencast mines and civil engineering works for the removal of overburden. Despite being very costly, they remain an integral part of the mines for almost 100 years due to their low overburden removal cost per tonne of coal. Their ability to excavate very deep down the earth makes them very effective and important in the mining industry. They can dig up to 450 tons of material in a single cycle. During a typical dragline cycle machine undergoes various types of motion and experiences static as well as dynamic load on its front end assembly parts which may lead to the failure of such components if not properly maintained on a regular basis. In the current research paper, a dragline boom model is created and analysed for stresses acting on it during static conditions by performing finite element analysis in SolidWorks simulation software. Afteranalyzing stresses, their locations are studied. Based on the simulation results the overall structural behaviour of the dragline boom can be predicted. © 2019, Books and Journals Private Ltd. All rights reserved.